2016
DOI: 10.1248/yakushi.15-00222
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Association of Hand-Foot Syndrome with Anticancer Drugs Using the US Food and Drug Administration Adverse Event Reporting System (FAERS) and Japanese Adverse Drug Event Report (JADER) Databases

Abstract: 有害事象自発報告データベース(JADER 及び FAERS)を用いた抗がん剤と手足症候群の検討 笹岡沙也加, a 松井利亘, a 阿部純子, a,b 梅津亮冴, c 加藤大和, a 上田夏実, a 羽根由基, a 元岡佑美, a 畠平春奈, a 紀ノ定保臣, d 中村光浩 ,a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Sasaoka et al reported that in their study of the time to onset for hand-foot syndrome during treatment with anticancer agents, for which they used JADER and FAERS, the input ratio of SAEs with capecitabine was 78% in JADER and 49% in FAERS. 8 The reporting ratios of time-to-onset information with TNF-I and IL-6-I in our study were similar to that for capecitabine in the previous study, but the ratio for MTX was lower. We suspect that because MTX had been administered as off-label use long before the approval for the RA indication, the safety profile of MTX was considered to have been established to some extent.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Sasaoka et al reported that in their study of the time to onset for hand-foot syndrome during treatment with anticancer agents, for which they used JADER and FAERS, the input ratio of SAEs with capecitabine was 78% in JADER and 49% in FAERS. 8 The reporting ratios of time-to-onset information with TNF-I and IL-6-I in our study were similar to that for capecitabine in the previous study, but the ratio for MTX was lower. We suspect that because MTX had been administered as off-label use long before the approval for the RA indication, the safety profile of MTX was considered to have been established to some extent.…”
Section: Discussionsupporting
confidence: 88%
“…As studies that focused on the time to onset of AEs from drugs, investigations of suicide or diabetes with interferon formulations, osteonecrosis of the jaw with bisphosphonates, and hand-foot syndrome with anticancer agents have been reported. [8][9][10][11] Weaknesses of spontaneous-report databases, such as overreporting, underreporting, and missing data have been pointed out. 9,12 Since JADER is a spontaneous-report database, we need to recognize the existence of selection bias and reporting bias, and that some data are missing.…”
Section: Introductionmentioning
confidence: 99%
“…Median, quartile, and Weibull shape parameter (WSP) tests were used to evaluate the time-to-onset analysis [710]. We analyzed the time the specific adverse event occurred from when the prescription of specific drugs commenced by using the Weibull distribution parameter.…”
Section: Methodsmentioning
confidence: 99%
“…If β is greater than 1 and the 95% CI of β excludes the value of 1, the hazard is considered to increase over time. [17][18][19][20]24,25) We investigated the relation between the number of reports and seasonality of DIP. We analyzed the onset day of AEs and then obtained the number of AE reports per month between April 2004 and November 2016 from REAC table of JADER.…”
Section: 23)mentioning
confidence: 99%